Activation of Peracetic Acid with CuFe2O4 for Rhodamine B Degradation: Activation by Cu and the Contribution of Acetylperoxyl Radicals - Chengzhi Yu; Libin Zheng; Yongyuan Hong; Jiabin Chen; Feng Gao; Yalei Zhang; Xuefei Zhou; Libin Yang (Molecules, 2022)
Advanced oxidation processes (AOPs) demonstrate great micropollutant degradation efficiency. In this study, CuFe2O4 was successfully used to activate peracetic acid (PAA) to remove Rhodamine B. Acetyl(per)oxyl radicals were the dominant species in this novel system. The addition of 2,4-hexadiene (2,4-HD) and Methanol (MeOH) significantly inhibited the degradation efficiency of Rhodamine B. The ≡Cu2+/≡Cu+ redox cycle dominated PAA activation, thereby producing organic radicals (R-O˙) including CH3C(O)O˙ and CH3C(O)OO˙, which accounted for the degradation of Rhodamine B. Increasing either the concentration of CuFe2O4 (0–100 mg/L) or PAA (10–100 mg/L) promoted the removal efficiency of this potent system. In addition, weakly acid to weakly alkali pH conditions (6–8) were suitable for pollutant removal. The addition of Humid acid (HA), HCO3−, and a small amount of Cl− (10–100 mmol·L−1) slightly inhibited the degradation of Rhodamine B. However, degradation was accelerated by the inclusion of high concentrations (200 mmol·L−1) of Cl−. After four iterations of catalyst recycling, the degradation efficiency remained stable and no additional functional group characteristic peaks were observed. Taking into consideration the reaction conditions, interfering substances, system stability, and pollutant-removal efficiency, the CuFe2O4/PAA system demonstrated great potential for the degradation of Rhodamine B.